Adiantum Capillus Veneris L.: From Iranian Traditional Medicine to Modern Phytotherapy - Nastaran Ebadi; Fatemeh Farjadmand; Mozhgan MehriArdestani; Fahimeh Mohajerani; Azadeh Raies-Dana; Zahra Shahpiri; Roja Rahimi (Tehran University of Medical Sciences, 2016)
Adiantum Capillus veneris L. from the family Polypodiaceae, is one of the medicinal herbs used in  Iranian traditional  medicine (ITM).  It has been identified as "Parsiavashan"  in  Iranian traditional medicine and commonly known as "Maidenhair fern" in English. Triterpenoids and flavonoids are the major compounds identified in Maidenhair fern. It has been used in Iranian traditional medicine for treating respiratory tract diseases, irregular menstruation, flatulence, jaundice, splenomegaly and scrofula. It has been topically used in skin and hair disorders, too. The pharmacological activities reported from this plant are anti-inflammatory, antinociceptive, antimicrobial, antidiabetic, diuretic and antioxidant. However, there is not direct relationship between pharmacological activities of this plant in Iranian traditional medicine and modern phytotherapy; the anti-inflammatory and antimicrobial properties of this plant could make it useful for respiratory tract disorders. Anyway, it is recommended to design experimental and clinical studies on pharmacological activities and indications of Adiantum capillus veneris mentioned in Iranian traditional medicine literatures